Enhanced strengthening and hardening via self-stabilized dislocation network in additively manufactured metals. (November 2021) - Li, Zan; Cui, Yinan; Yan, Wentao; Zhang, Di; Fang, Yan; Chen, Yujie; Yu, Qian; Wang, Ge; Ouyang, Heng; Fan, Chen; Guo, Qiang; Xiong, Ding-Bang; et al.
Graphical abstract: Abstract: The advent of additive manufacturing (AM) offers the possibility of creating high-performance metallic materials with unique microstructure. Ultrafine dislocation cell structure in AM metals is believed to play a critical role in strengthening and hardening. However, its behavior is typically considered to be associated with alloying elements. Here we report that dislocations in AM metallic materials are self-stabilized even without the alloying effect. The heating–cooling cycles that are inherent to laser power-bed-fusion processes can stabilize dislocation network in situ by forming Lomer locks and a complex dislocation network. This unique dislocation assembly blocks and accumulates dislocations for strengthening and steady strain hardening, thereby rendering better material strength but several folds improvements in uniform tensile elongation compared to those made by traditional methods. The principles of dislocation manipulation and self-assembly are applicable to metals/alloys obtained by conventional routes in turn, through a simple post-cyclic deformation processing that mimics the micromechanics of AM. This work demonstrates the capability of AM to locally tune dislocation structures and achieve high-performance metallic materials.